2018
DOI: 10.2134/agronj2018.01.0003
|View full text |Cite
|
Sign up to set email alerts
|

Defoliation Management Affects Productivity, Leaf/Stem Ratio, and Tiller Counts of ‘Performer’ Switchgrass

Abstract: Core Ideas Defoliation management resulted in a wide range of plant responses that varied by year, with deleterious responses more evident in the second year. Greater leaf/stem ratios occurred with more frequent defoliation treatments. Frequent defoliations such as every 3 wk should maintain a stubble height of at least 40 cm, defoliation frequencies ≥6 wk to 20‐cm stubble height, and ≥9 wk to 10 cm stubble height are warranted to ensure stand persistence. ‘Performer’ switchgrass (Panicum virgatum L.) was rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(31 citation statements)
references
References 24 publications
6
25
0
Order By: Relevance
“…A detailed description of plot management was provided by Bekewe et al (2018). A 50-by 51-m area of well-established (>8 yr) 'Performer' switchgrass was used for this experiment.…”
Section: Experimental Site and Plot Managementmentioning
confidence: 99%
See 4 more Smart Citations
“…A detailed description of plot management was provided by Bekewe et al (2018). A 50-by 51-m area of well-established (>8 yr) 'Performer' switchgrass was used for this experiment.…”
Section: Experimental Site and Plot Managementmentioning
confidence: 99%
“…In addition, they reported that overutilization of the grass at the start of the growing season, such as clipping monthly for three consecutive months starting in May, resulted in lower yields, lower tiller numbers, and weed infestation, to the point that weeds shaded the switchgrass tillers. Bekewe et al (2018) indicated that frequently defoliated treatments had lower DM yield and required clipping to greater stubble heights to ensure productivity and persistence of 'Performer' switchgrass. Working with 'Alamo' switchgrass, Seepaul et al (2014) reported concurrent lower canopy heights at harvest and lower total herbage mass for treatments that were frequently clipped to a stubble height of 5 cm.…”
Section: Canopy Heightmentioning
confidence: 99%
See 3 more Smart Citations